The Plan of Iguala as a Fundamental Law of the Independent Mexican State - del Arenal Fenochio, Jaime (2021)
In the origins of the Mexican State as an independent constitutional state it cannot be ignored that one of its juridical-political pillars was the Plan of Iguala signed by Iturbide on February 24, 1821 understood, in the language of its time, precisely as a fundamental law which until now has not been recognized for ideological reasons. The concept of “Basic Law” is reviewed and concluded by qualifying this political project as one of the four fundamental laws at the origin of the independent Mexican State.